Answer:
1038
Step-by-step explanation:
you add 308 and 730
Wouldn't the ratio from length to width be 8?
Answer:
x = 8 and y = 5
Step-by-step explanation:
2x - 3y = 1 --(1)
x + 2y = 18
x = 18 - 2y --(2)
sub (2) into (1):
2(18 - 2y) - 3y = 1
36 - 4y - 3y = 1
-7y = 1 -36
7y = 35
y = 5
x = 18 - 2(5) = 8
Answer:
X = 25
Step-by-step explanation:
Set up as a ratio:
Simplify ratio, multiply by 5, divide by 12
![\frac{60}{144} = \frac{x}{60} \\\frac{5}{12}=\frac{x}{60} \\ 300 = 12x\\12x=300\\x=25](https://tex.z-dn.net/?f=%5Cfrac%7B60%7D%7B144%7D%20%3D%20%5Cfrac%7Bx%7D%7B60%7D%20%5C%5C%5Cfrac%7B5%7D%7B12%7D%3D%5Cfrac%7Bx%7D%7B60%7D%20%5C%5C%20300%20%3D%2012x%5C%5C12x%3D300%5C%5Cx%3D25)
Answer:
y = -27
Step-by-step explanation:
- Multiply the entire equation by 6
![\sf 6*\dfrac{y+1}{3}-6*\dfrac{3y-1}{6}=6*5\\\\\\](https://tex.z-dn.net/?f=%5Csf%206%2A%5Cdfrac%7By%2B1%7D%7B3%7D-6%2A%5Cdfrac%7B3y-1%7D%7B6%7D%3D6%2A5%5C%5C%5C%5C%5C%5C)
2*(y + 1) - (3y - 1 ) = 30
- Multiply (y +1) by 2 and (3y - 1) by (-1)
2y + 2 - 3y + 1 = 30
- Isolate y term by taking the constant term to RHS
2y - 3y = 30 - 2 - 1
-y = 27
y = -27